1991
DOI: 10.1111/j.1464-410x.1991.tb15065.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Urological Malignancy in Zambia A Hospital‐based Histopathological Study

Abstract: The pattern of urological malignancy among the indigenous population of Zambia (determined on the basis of histopathological reports from a major national hospital during an 8-year period) is presented. A total of 6514 malignancies were observed, of which 784 (12%) were of urological origin. Bladder carcinoma, predominantly squamous type, was the commonest urological tumour (51%), followed by carcinoma of the prostate (26%), carcinoma of the penis (18%), renal tumours (4.3%) and testicular malignancy (0.7%). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
8
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
3
8
1
Order By: Relevance
“…The relatively younger age of our male patients with bilharzial cancer is in agreement with reports from other endemic areas [2,5,17]. The comparison was not valid in females due to the small number.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The relatively younger age of our male patients with bilharzial cancer is in agreement with reports from other endemic areas [2,5,17]. The comparison was not valid in females due to the small number.…”
Section: Discussionsupporting
confidence: 80%
“…Six (46%) had BC which remains lower than that from Egypt due perhaps to the sparse farming in the Tihama lowlands compared to Egypt. Al-Shukri et al [16] also reported a 75% BC rate from Kuwait where most of the patients were foreign workers originating from high bilharzial endemic areas.The relatively younger age of our male patients with bilharzial cancer is in agreement with reports from other endemic areas [2,5,17]. The comparison was not valid in females due to the small number.…”
supporting
confidence: 80%
See 3 more Smart Citations